(untitled) (Al-Academy, 2022)
The subject of the act and its transformations in the presentation is of great importance at the level of study, analysis and interpretation, and through that the researcher adopted the following title (The Dramatic Act and Its Transformations in the Iraqi Theatrical Show). The play of Black Astronomy was chosen as a sample for analysis, and the aim of the research came in order to achieve a special knowledge of the extent of the transformation that occurred between the dramatic structure of the act and theatrical embodiment and its multiple elements of operation in the Iraqi theatrical shows. It was limited to the show of the Iraqi theater in the year (2020) and included the theoretical framework that accommodated three sections. As for the first section: stage of dramatic act construction in the text. The researcher studied the concept of the dramatic act and its construction stages. And the second section: the elements of the action of the dramatic act in the show, while the third topic was entitled transformations of the dramatic act in the Iraqi theatrical show, and the researcher concluded the second chapter with what the framework resulted in considering indicators as suggested starting points and a tool for analyzing the sample, and then the research procedures that included The research sample, and then analyzing the sample for the play (Black Astronomy) by Iraqi director Riyad Shaded, and the researcher analyzed it according to the descriptive approach in the style of (content analysis) to reach the results of the research, including (crystallization and construction of the dramatic act according to a doctrine, method, or a specific theatrical direction that gives space Extensive space to operate according to disciplined mechanisms that are not tainted by fragmentation or distortion.), then conclusions, recommendations, suggestions and a list of sources.